Pengembangan Modul berbasis Problem Based Learning untuk Meningkatkan Pengetahuan Metakognitif Peserta Didik pada Materi Suhu dan Kalor - Al Farizi, Taufiq; Alatas, Fathiah; Jannah, Ni’matul (Jurnal Penelitian Pembelajaran Fisika, 2023)
The purpose of this study is to develop a problem-based learning module to create valid, effective, and practical materials on the concepts of temperature and heat that will help students improve their metacognitive knowledge. The ADDIE development model used in this study. The research subjects were students of class XI SMAN 11 Maros who became the subjects of this research. The instruments used are tests in the form of cognitive and metacognitive knowledge and non-tests in the form of questionnaires and interviews. The results of the study based on linguistic experts amounted to 88.1, media experts amounted to 85.26, material experts amounted to 91.07 with a very valid category. The results of the effectiveness of the module by physics teachers are 98.95 and students are 88.79 in the very practical category. The results of the effectiveness in increasing metacognitive knowledge with an N-gain value of 0.4 in the medium category. This research obtained that the PBL-based module that has been developed is valid, practical, and effective to increase metacognitive knowledge on the concepts of temperature and heat.Keywords: metacognitive, problem based learning, temperature and heat.